HAS EVERYTHING TO BE DONE BY FORCE OF WAR AND BLOOD?... REFLECTIONS ON THE PACIFICATION OF AMERICA IN THE SPANISH PUBLIC DEBATE OF 1821 (Tzintzun, Revista de Estudios Históricos, 2024)
During the second spanish liberal experience, the press played a crucial role as a space for analysis,discussion, debate, and controversy that simmered in the highest spheres of power, including thecomplex and ever-changing issue of American dissent and the desired independence. Theprominence of both public opinion and public debate was evident. In this tumultuous context ofmid-1821, the development of political journalism as a groundbreaking revelation contributedto the formation of identities and the construction of political life in both Spain and America.This article highlights the public debate on the pacification of America and the paths that shouldbe forged for a post-independence relationship, although the focus is particularly on the reveredNew Spain, a perennial concern in this conflict. The participating columnists freely expressedtheir opinions and offered solutions to the sensitive problem under discussion, exerting anunavoidable influence on public opinion and generating debates on how to put an end to thebloody effusion that had overshadowed the region for over a decade. At least within a sector ofSpanish society, there was hope of finding a path towards lasting peace and a promising futurefor the Spanish territories on both sides of the Atlantic.
Keywords: Press; public opinion; pacification; independence; war; New Spain